2013
DOI: 10.1002/rnc.2966
|View full text |Cite
|
Sign up to set email alerts
|

Output feedback control of a class of feedforward nonlinear systems in the presence of sensor noise

Abstract: We propose an output feedback controller for a class of feedforward nonlinear systems under sensor noise. The sensor noise is any signal whose DC component is finite, which covers not only deterministic signals but also random signals including many practical noises. We introduce a notion of virtual state, then propose a measurement output feedback controller that utilizes a gain scaling factor. The gain scaling factor is commonly employed by the observer and controller. Through analysis, we show that all syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Without loss of generality, we only consider the communication topology graph given in Case 2. As that in , here the zero‐mean white noise signal with |si(t)|trues̄ is used. In simulation, the white noise is generated from MATLAB (MathWorks, Inc., Natick, MA, USA) based on uniformly distributed random numbers.…”
Section: Numerical Examples and Simulationsmentioning
confidence: 99%
“…Without loss of generality, we only consider the communication topology graph given in Case 2. As that in , here the zero‐mean white noise signal with |si(t)|trues̄ is used. In simulation, the white noise is generated from MATLAB (MathWorks, Inc., Natick, MA, USA) based on uniformly distributed random numbers.…”
Section: Numerical Examples and Simulationsmentioning
confidence: 99%
“…Output feedback control problems have received much attention and a number of research results for nonlinear systems have been reported, eg, in other works . In the work of Choi and Lim, authors proposed an adaptive output feedback control scheme, which can deal with both triangular or feedforward nonlinear systems with unknown linear growth rate in a unified framework for global stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…The controller was coupled with a low-pass filter to attenuate the effect of sensor noise and rendered the system state ultimately bounded. Compared with [1], the condition of sensor noise in [2] was not limited to deterministic periodic signals and allowed to be a random signal having nonzero-mean. By introducing a notion of virtual state and using high-gain observer technique, the authors proposed a scaled output feedback controller for a class of feedforward system to render that all the system states and output remained to be bounded in the presence of sensor noise.…”
Section: Introductionmentioning
confidence: 99%
“…There exist some drawbacks in the design schemes of [1][2][3][4][5][6][7][8], that is, the effect of sensor noise on the system performance is only reduced not eliminated and sensor noise cannot be reconstructed. Besides, actuator fault is not considered.…”
Section: Introductionmentioning
confidence: 99%